Ultra-Wideband 4-Bit Distributed Phase Shifters Using Lattice Network at K/Ka- and E/W-Band - Sungwon Kwon; Minjae Jung; Byung-Wook Min (IEEE Open Journal of the Solid-State Circuits Society)
In this article, we introduce an ultra-wideband 4-bit distributed phase shifter using a lattice network. To achieve wider bandwidth, the proposed phase shifter employed an all-pass lattice network instead of the traditional low-pass ladder network. Seven cascaded 22.5° lattice phase shifters and one switched line 180° phase shifter were used to achieve 360° phase shift range. Based on our theoretical analysis, we designed the lattice network as a constant-phase shifter rather than a delay line. Implementations in the K/Ka- and E/W-bands validate the suitability of the lattice network for constant-phase shifting. Fabricated using 28-nm bulk CMOS technology, the K/Ka-band phase shifter had a size of 0.45 mm2 excluding pads. Within the frequency range of 20.5–35.5 GHz, the root-mean-square (RMS) phase error ranged from 1.6 to 5°, the RMS gain error ranged from 0.3 to 0.6 dB, and the return loss remained above 10 dB. At 28 GHz, the insertion loss was $11.6± 0$ .8 dB without dc power consumption. Fabricated using 28-nm FD-SOI technology, the E/W-band phase shifter had a size of 0.3 mm2 excluding pads. Within the frequency range of 63.5–100.5 GHz, the RMS phase error ranged from 2.4 to 4.6°, the RMS gain error ranged from 0.44 to 1 dB, and the return loss remained above 10 dB. At 82 GHz, the insertion loss was $11.9± 1$ .1 dB without dc power consumption. The proposed phase shifter demonstrated exceptional performance for multistandard operation, achieving low RMS phase and gain errors across a wide fractional bandwidth of 53.6% and 45.1%, respectively.